Pengetahuan Personal Hygiene Remaja Putri pada Kasus Keputihan - Helmy Ilmiawati; Kuntoro Kuntoro (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2016)
This study was a cross sectional study. This research was conducted at the Institute of Islamic Education Nurul Haromain “SMP Plus Fityani" Ngroto village Pujon Malang. The purpose of this study to determine how personal hygiene knowledge of young women with vaginal discharge cases experienced. Researchers used 50 respondents and all met the inclusion criteria. Sampling method was used total sampling. The variables studied were respondent characteristics include age and educational level. While the variable knowledge of personal hygiene includes washing hands before touching the genitals, vagina washing the right way, the use of underwear, the use of pantyliener. For the case of white discharge is white discharge experienced by respondents. All variables were measured using the enclosed questionnaire and analyzed using descriptive analysis. The results most of the characteristics of the age of respondents was 13 years old. The results of the knowledge of personal hygiene mostly young girls who do not have a good knowledge of 23 respondents (46%) of personal hygiene. For the case of white discharge experienced by most experienced white discharge was abnormal discharge in the amount of 27 respondents (54%). Knowledge wasn't good due to limited access to information and a facilitator at the Education Institute. If left unchecked it will cause serious reproductive health problems. So, we need a facilitator in order to solve these problems.